Two-dimensional direction-of-arrival estimation and pairing using L-shaped arrays. Issue 8 (November 2016) - Ta, Shiying; Wang, Hongqiang; Chen, Haowen
Abstract This paper proposes a computationally efficient azimuth and elevation estimation and pairing method using L-shaped uniform arrays. The azimuths and elevations of the incident signals are estimated independently at first using the outputs of the two array arms via equation rooting, which well avoids the computationally demanding spatial scanning procedure contained in most of the previous direction-of-arrival estimation methods. The order of the equations equals the number of the incident signals; thus, this procedure is computationally very cheap and can be implemented using various numeric algorithms. Then two optional methods are proposed for azimuth–elevation pairing. One method exploits the cross-correlation of the two subarray outputs of the L-shaped array, and the other method is realized by estimating the signal powers based on the direction estimates. Both of the two direction-pairing methods are implemented using numerical computations; thus, this procedure is also computationally very cheap. In-depth analyses are provided on the selection of the two optional azimuth–elevation pairing methods in different environments. Numerical examples are carried out to demonstrate the performance of the proposed method.